2022
DOI: 10.1186/s12964-022-00917-0
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways, microenvironment, and targeted treatments in Langerhans cell histiocytosis

Abstract: Langerhans cell histiocytosis (LCH) is an inflammatory myeloid malignancy in the “L-group” histiocytosis. Mitogen-activated protein kinase (MAPK) pathway activating mutations are detectable in nearly all LCH lesions. However, the pathogenic roles of MAPK pathway activation in the development of histiocytosis are still elusive. This review will summarize research concerning the landscape and pathogenic roles of MAPK pathway mutations and related treatment opportunities in Langerhans cell histiocytosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…LCH comprises qualities of both neoplasia and immunogenic components, and in ammation also plays a vital role in the pathophysiology of LCH [33][34][35]. LCH lesions are accompanied by a diverse in ammatory in ltrate, enriching dysfunctional T cells [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…LCH comprises qualities of both neoplasia and immunogenic components, and in ammation also plays a vital role in the pathophysiology of LCH [33][34][35]. LCH lesions are accompanied by a diverse in ammatory in ltrate, enriching dysfunctional T cells [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…LCH comprises qualities of both neoplasia and immunogenic components, and inflammation also plays a vital role in the pathophysiology of LCH [33][34][35] . LCH lesions are accompanied by a diverse inflammatory infiltrate, enriching dysfunctional T cells [36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that BRAF V600E mutation leads disruption of endogenous host immune surveillance, immune escape of tumors, and anti-apoptotic activity (7,10).…”
Section: Discussionmentioning
confidence: 99%
“…LCH can be seen in one or more than one organs and can be unifocal or multifocal (2,5,6). Skull involvement is also considered as a risky localization since it comprises risk for diabetes insipidus and degenerative disease (7,8). LCH manifests as an inflammatory lesion in any tissue.…”
Section: Introductionmentioning
confidence: 99%